Preliminary Study into the Application of Metabolomics in Soil Discrimination - Salaudeen, Abdulwasiu Olawale; Olawore, Yemisi Ajoke; Yetunde, Aishat Abdulkareem; Yakubu, Hajara; Dewa, Abubakar Umar (Darul Yasin Al Sys, 2025)
Soil metabolomics provides a comprehensive analysis of small-molecule metabolites (≤1.5 kDa) present in soil and offers insights into how environmental processes influence soil conditions. Although this technique has been applied to various soil-related studies, it remains underrepresented in the broader field of metabolomics, highlighting the need for further research. This study aims to characterize the soil metabolome across contrasting soil sites to evaluate the discriminating capacity of soil metabolomics and its potential as a soil quality indicator. Soil metabolites were extracted using methanol and dichloromethane and analyzed with an Agilent 1260 Infinity II liquid chromatography–mass spectrometry platform. A total of 307 compounds were positively identified, including steroids, saponins, amino acids, organothiophosphorus compounds, and fatty acids. Multivariate statistical tools, such as Partial Least Squares Discriminant Analysis (PLS-DA) score and loading plots, Variable Importance in Projection (VIP) scores, Significance Analysis of Microarrays (SAM), and heat mapping successfully discriminated the soil samples from four distinct sites. Among the identified metabolites, prolyl-hydroxyproline (ID 1817) had the highest VIP score (≈2.62) and emerged as a potential biomarker for differentiating soil types. These findings underscore the utility of metabolomics in soil characterization and its potential application in environmental monitoring and soil quality assessment.